Model Pemberdayaan UMKM Berbasis Masjid - Faisal, Andi; Kurnia M, Fakhruddin (Jurnal Iqtisaduna, 2023)
This research explores the MSME empowerment model carried out by mosque managers. The study was designed using a qualitative method. The research design used an interpretive paradigm to describe and understand social situations, interactions, and the role of the research object's actions in empowering the community's economy. Ernams in Robiatul argues that the interpretive paradigm is a social system that interprets behaviour in detail by directly observing. The approach used in this study is phenomenological. The object of this research is the Great Mosque of Sidrap and several other mosques. Data collection techniques using observation, interviews and documentation. The study results show that the MSME empowerment model carried out by mosque managers is by building a sharia cooperative system using the concept of profit sharing. Sharia cooperatives based on the type of savings and loan business can be implemented using the idea of mudharabah, and sharia cooperatives based on the type of product business or the sale of staple goods can be implemented using the musyarakah concept. Keywords: Role Model, Empowerment, MSMEs, Mosque Empowerment